A novel method for rotor field-oriented control of single-phase induction motor - Jannati, Mohammad (Institute of Advanced Engineering and Science, 2015)
This paper presents a novel rotor field-oriented control (RFOC) method for asymmetrical single-phase induction motor (SPIM). It is shown in this paper that by using a suitable transformation matrix (TM) for stator current variables, the asymmetrical equations of SPIM are transformed into symmetrical equations. Based on this similarity, a novel vector conrol technique for SPIM is presented. Performance of the proposed method is assessed using MATLAB/SIMULINK software. Simulation results showed the excellence speed and torque responses obtained using the proposed technique.